Parent's Perception of The Development of The Building Character of Integrated Islamic Elementary School Students In Al-Uswah Pamekasan - Budianto, Ahmad Andry; Amin, Agus Saifuddin; Hidayat, Tawvicky (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
Nowadays, character education in schools has received special attention by the government through the Ministry of Education and Culture Research Technology. The character of the education promoted by the government is integrated with formal education from the elementary schools, junior high schools and senior high schools levels, the presence of character education is expected to have a positive impact on the development of students in schools. According to Ryan & Bohlin (1999) character is a pattern of individual behavior, if the individual has good character, he has an understanding of goodness, likes goodness and does good. This research was conducted at the Integrated Islamic Elementary School (SDIT) Al Uswah Pamekasan with a sample of 42 parents, the method used in this research is descriptive quantitative research method using percentages. Based on the results of data analysis, it was found that the parents perception of the character building development of students was 90%. It is concluded that the parents perception is tremendous on the character building development of the Al Uswah Pamekasan Integrated Islamic Elementary School (SDIT) students. From these results, it is concluded that the character of Al Uswah Integrated Islamic Elementary School (SDIT) students has independence, has good behavior towards teachers and peers, maintains cleanliness and speaks politely.